Analysis of Customer Relationship Management , Service Quality and Brand Trust on Congregation Satisfaction : (Survey on Congregations of Pt. Amanah Putra Wisata Tour & Travel Sukabumi) - Ermawan, Muhammad Rifa; Sunarya, Erry; Komariah, Kokom (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the effect of Customer Relationship Management (CRM), service quality, and brand trust on congregation satisfaction of PT Amanah Putra Wisata Tour & Travel Sukabumi. The method used is a quantitative approach with associative research type. A sample of 218 respondents was selected using purposive sampling method. Data analysis techniques include multiple linear regression, T test, F test, and coefficient of determination processed using SPSS 26. The results showed that simultaneously, CRM, service quality, and brand trust had a significant effect on congregation satisfaction. However, partially, only service quality and brand trust are proven to have a positive and significant effect on congregation satisfaction. Although the CRM variable has a positive influence, it is not statistically significant. Brand trust is the most dominant variable in influencing congregation satisfaction. These results indicate that improving service quality and strengthening the brand can be the main strategy in increasing customer satisfaction in the Umrah worship travel service industry.